2013
DOI: 10.1149/2.123306jes
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the ORR Using the Double-Trap Intrinsic Kinetic Model

Abstract: The oxygen reduction reaction remains the main contributor to performance loss in polymer electrolyte fuel cells. A major challenge facing researchers is the development of a kinetic model that is simple and yet can accurately predict reaction rates at arbitrary electrode potentials. Recently, the double-trap intrinsic kinetic model was proposed. The model assumes that the overall reaction is comprised of four intermediate reactions and two intermediate adsorbed species. The model has been shown to predict the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
64
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(66 citation statements)
references
References 59 publications
2
64
0
Order By: Relevance
“…27 in Ref. 29 showed that the oxygen reaction order changed with overpotential and it did not agree with our proposed modified double trap model. Markiewicz et al 30 on the other hand reported that the reaction order did not change with overpotential over a range of 0.6 V. They measured the oxygen reduction reaction (ORR) kinetics using a floating electrode instead of an MEA.…”
mentioning
confidence: 78%
“…27 in Ref. 29 showed that the oxygen reaction order changed with overpotential and it did not agree with our proposed modified double trap model. Markiewicz et al 30 on the other hand reported that the reaction order did not change with overpotential over a range of 0.6 V. They measured the oxygen reduction reaction (ORR) kinetics using a floating electrode instead of an MEA.…”
mentioning
confidence: 78%
“…For both the HOR and ORR, α is typically taken to be equal to 1,115,116,[119][120][121] however newer models use a value between 0.5 and 1 (with significant cell-performance prediction changes) for the ORR due to Pt-oxide formation as examined in more detail below. [122][123][124][125] In addition, as mentioned, the choice of the reference potential for the overpotential will directly impact the exchange-current density (since they cannot be separated) and even reaction order. 115 Due to the importance of the ORR, more detailed kinetic expressions have been developed as described briefly below.…”
Section: Basic Governing Equationsmentioning
confidence: 99%
“…131 In this framework, the adjustable kinetic parameters are four activation and two adsorption free energies, which are fit to kinetic polarization data and cyclic-voltammetry data for surface oxide coverage, [137][138][139] or they can be estimated computationally by ab-initio modeling. 124,139,140 A double-trap modeling framework offers a versatile way to model the PEFC's reaction kinetics (provided good data for the fitting parameters is available), and it predicts the observed doubling of the Tafel slope due to reaction-pathway changes and captures the trends of the experimental oxide coverage. It can also has a capability to bridge the more traditional kinetic models with the theoretical results from ab-initio studies.…”
Section: Basic Governing Equationsmentioning
confidence: 99%
See 1 more Smart Citation
“…e ∈ {an, ca} [5] where the first term is due to condensation and the second term is due to the liquid water intrusion from the GDL. The saturation pressure is given by the following empirical fit:…”
Section: Mathematical Model Developmentmentioning
confidence: 99%